REPRESENTASI BERITA PENISTAAAN AGAMA DALAM MEDIA MASSA DI INDONESIA - Muhamad Fahmi (IAIN Salatiga, 2018)
This article wants to see how the representation of mass media in Surakarta, namely Solopos and Joglosemar, in the case of the establishment of Religion by Basuki Cahaya Purnama (Ahok). The method used is Theo van Leuwen's critical discourse analysis which focuses on how actors are inclusion and exclusion in media news. The results of this study explain that: (1) Pos Solo sided with Ahok. Ahok is excluded (omitted, blurred from narrative text) when it comes to negative information and vice versa, inclusion (made clear) if positive news information for Ahok. (2) Joglosemar also seems to support Ahok. Joglosemar uses exclusion and passivation techniques. The use of these two techniques is done while giving